Permanent Antimicrobial Poly(vinylidene fluoride) Prepared by Chemical Bonding with Poly(hexamethylene guanidine) - Chen, Fuxiu (ACS Omega, 2020)
[Image: see text] Biofouling is one of the major obstacles in the application of poly(vinylidene fluoride) (PVDF) membrane in water and wastewater treatment. Developing antimicrobial PVDF could kill the attached microbe in the initial stage, thus theoretically inhibiting the formation of biofilm and delaying the occurrence of biofouling. However, the leaching of the antimicrobial component and deterioration of antimicrobial properties remain a concern. In this work, an antimicrobial PVDF (PVDF-g-AGE-PHMG) was developed by chemical bonding PVDF with poly(hexamethylene guanidine hydrochloride) (PHMG). The obtained PVDF-g-AGE-PHMG was blended with pristine PVDF to prepare an antimicrobial PVDF membrane. The results of Fourier transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) confirmed that PHMG was successfully grafted into the PVDF membrane. The morphologies, membrane porosity, water contact angles, antimicrobial properties, mechanical properties, and thermostability of the as-prepared membranes were investigated. When the content of PVDF-g-AGE-PHMG reached 10.0 wt %, the inhibition rates of both antimicrobial PVDF membrane against Escherichia coli and Staphylococcus aureus were above 99.99%. Due to the increased hydrophilicity, excellent antimicrobial activity, nonleaching of antimicrobial component, good mechanical properties, and thermostability, the as-prepared PVDF membrane has promising applications in the field of water treatment.